Dahu Lake paleoclimate data - Abdur Rahman (16982805) (2025)
The Dahu_Lake_data.xlsx contains three sheets: Organic, Geochemical, Diatom, and 14C. The Organic sheet includes carbon and nitrogen contents, elemental ratios, and the carbon isotopic composition of organic matter in core sediments from Dahu Lake, northern Taiwan. These proxies were used to infer changes in organic matter sources, which provided insights into runoff conditions and helped identify typhoon events in the region. The Geochemical sheet contains the concentrations of leached elements (K, Mn, Na, Sr, Ti, Al, Fe) and K/Na ratios in core sediments. This data helped track changes in the intensity of chemical weathering in the region, supporting the interpretations derived from the organic data. The Diatom sheet presents the abundances of diatoms categorised by their preferred habitats, including planktonic, benthic, and epiphytic species, along with their total concentrations in the core sediments. The 14C sheet contains the radiocarbon ages of the samples at different depths using different materials. Abstract of the Manuscript To enhance the understanding of the Holocene climate in northern Taiwan, where early to mid-Holocene paleoclimate data is sparse, a study was designed to collect a lake core from Dahu Lake in the Ilan Plain, located in the northeastern part of Taiwan. To investigate the climate, a multiproxy approach was employed, examining geochemical elements, diatoms, total organic carbon (TOC), total nitrogen (TN), their ratios (TOC/TN), and carbon isotopic compositions (δ¹³Corg). Diatom data indicated that the area primarily functioned as a riverine system, with occasional time frames of lake level situations during 6.6, 5.0, 3.7, 2.1, 1.0, and 0.4–0.2 cal kyr BP. The multiproxy analysis, which included TOC, TN, TOC/TN, and δ¹³Corg, suggested substantial terrestrial input. Elevated levels of Ti and the presence of illite pointed to sporadic overflow from the Lanyang River. Additionally, high K/Na ratios indicated intense chemical weathering. These combined findings implied increased typhoon activity during the periods 7.7–4.9, 3.8–3.6, 3.3–2.8, 2.2–2.0, 1.2, 1.0, and 0.5–0.2 cal kyr BP. In contrast, the periods between these frequent typhoons or wetter climate events were relatively drier, as evidenced by sediments that primarily originated from the Ilan River. The typhoon activities were a response to a strong EASM and La Niña-like conditions in the Pacific Ocean. In contrast, the drier periods were characterized by strong EAWM and El Niño-like conditions in the region.